A Competence-Based Curriculum Design for Entrepreneurship Study Program - Siagian, Priska J.R.; Simatupang, Togar M. (Universitas Prasetiya Mulya, 2011)
Indonesia is affected by global crisis. Increasing the number of entrepreneurs is one of many solutions to increase the economic growth in Indonesia. The number of entrepreneurs in Indonesia to leverage the economic growth is still limited. Entrepreneurs can be prepared through an Entrepreneurship Study Program. Entrepreneurship Study Program attempts to create qualified entrepreneurs who have relevant competences. In order to create a qualified entrepreneurs, the Entrepreneurial Studies Program requires a competency-based curriculum that will support the educational process and provide all the necessary to become future entrepreneurs who can survive through a global challenge. This research aims to design a competence-based curriculum for entrepreneurial study and uses Quality Function Deployment (QFD) as the major tool to design the competencebased curriculum. From the QFD process, this research finds core and elective courses for the Entrepreneurship Study Program. The result shows the competences covered by the courses and sequence, credits, and teaching methods for each course. The competences prepared the potential entrepreneurs can be achieved through specific courses which can be acquired within 8 semesters.